Bahan Ajar Berbasis Problem Based Learning pada Materi Gerak Lurus untuk Meningkatkan Kemampuan Komunikasi dan Kolaborasi Siswa - Nurhayati, Dyah Isna; Yulianti, Dwi; Mindyarto, Budi Naini (UPEJ Unnes Physics Education Journal, 2019)
This research aims to produce teaching materials based Problem Based Learning to improve students? ability of communication and collaboration. This research used R&D method with the procedure of: introduction, plan program, product development. Trial design with one-Group pretest-posttest design, the subjects research class X MIPA 4 of SMA N 1 Juwana. This study aims to describe the characteristics of PBL-based teaching materials, test the level of feasibility, increase the ability of written communication, oral and collaboration, and student responses to teaching materials. The level of advisability and legibility in teaching material examine by the questionnaire and fill in the blank test. The data of ability improvement in written communication taken through the result of pretest and posttest, while the ability in spoken communication and collaboration taken through the result of observation. Students? response was taken through questionnaire after learning process. The results showed that the teaching materials based Problem Based Learning has a level of feasibility and good readability level and can improve students? ability of communication and collaboration.